The Use of Iraqi Probiotic and Poultrygrow 250 in Reducing the Experimentally Infection of Broiler Chicks with Salmonella Typhimurium: G. A. Al-Kaissy , E. J. A. Al-Ubaidi and R. A. Abd Al-Jalile - Al-Kaissy, G. A. (The Iraqi Journal of Veterinary Medicine, 2006)
The study was conducted to find out the effect of some feed additives inreducing the infection rate of broilers with Salmonella typhimurium.Forty broiler chicks at one week of age were divided into 4 treatments, 10chicks each as follows:T1: uninfected control.T2: Salmonella typhimurium infected + Iraqi Probiotic.T3: Salmonella typhimurium infected + Poultrygrow 250.T4: Salmonella typhimurium infected only.One day after feeding on feed additives, the birds were experimentallyinfected with Salmonella typhimurium through the mouth.Results show that Iraqi probiotic did not decrease the severity of infectionwith Salmonella typhimurium in comparison with those of Poultrygrow 250,shown by the percentage of mortality and number of Salmonella excreted withthe feaces. Poultrygrow 250 causes a significant (ρ < 0.01) increase in bodyweight, weight gain and feed conversion ratio through reducing feedconsumption. Iraqi probiotic has similar effect but for less extent.It was conducted that adding Poultrygrow 250 to the feed decreases theintensity of Salmonella typhimurium infection in broiler and improvesperformance.